Voluntary After-School Alcohol and Drug Programs for Middle School Youth : If You Build It Right, They Will Come - D’Amico, Elizabeth J. (2012)
Few after-school programs target alcohol and other drug (AOD) use because it is difficult to encourage a diverse group of youth to voluntarily attend. The current study describes attendance at a voluntary after-school program called CHOICE, which targeted AOD use among middle school students. Over 4,000 students across eight schools completed surveys and 15% participated in CHOICE. Analyses indicated that there were some differences between CHOICE participants and non-participants. For example, African American and multiethnic students were more likely to attend. Past month alcohol users were more likely to initially attend, and marijuana users were more likely to continue attendance. Thus, CHOICE reached students of different racial/ethnic groups and attracted higher risk youth who may not typically obtain prevention services.